(untitled) (Swiss Medical Weekly, 2025)
Technological advancements have significantly reshaped diabetes care. Diabetes and technology now encompass the hardware, devices and software required to treat diabetes mellitus. In Switzerland, these technologies are being increasingly adopted, especially by people living with type 1 diabetes, where continuous glucose monitoring (CGM) and automated insulin delivery (AID) systems are considered standards of care. This document provides a comprehensive overview of all diabetes-related technologies currently available in Switzerland. It details their technical specifications, indications for use across diverse populations, compatibility, reimbursement regulations and practical guidance for implementation. Recommendations extend to special populations: children and adolescents, pregnant women, older adults, and people with type 2 diabetes or other specific diabetes types (e.g. maturity-onset diabetes of the young [MODY] or pancreatogenic diabetes). In youth with type 1 diabetes, early adoption of continuous glucose monitoring and automated insulin delivery systems is strongly encouraged and is supported by the Swiss Society of Paediatric Endocrinology and Diabetology. During pregnancy, achieving and maintaining strict glycaemic targets is crucial for reducing pregnancy-related complications. Continuous glucose monitoring and automated insulin delivery improve glycaemic metrics and neonatal outcomes. In older adults, technologies can reduce hypoglycaemia risk and simplify management. For people with type 2 diabetes, continuous glucose monitoring and insulin pumps have shown benefits in glycaemic control, with growing evidence supporting the use of automated insulin delivery systems. The document also highlights the expanding role of telemedicine and remote monitoring. While offering greater accessibility and patient-centred care, these tools raise challenges in terms of digital literacy, interoperability and data protection. Finally, the integration of diabetes and technology into diabetes care requires structured education. Diabetes self-management education and support programmes such as Functional Insulin Therapy (FIT) are essential to help people acquire the knowledge and skills necessary to manage insulin therapy and use diabetes technology effectively and safely. Overall, these recommendations aim to support effective and equitable use of diabetes technology throughout Switzerland and to guide healthcare providers, patients and policymakers towards improving diabetes outcomes.